2024
DOI: 10.1021/acs.langmuir.3c03043
|View full text |Cite
|
Sign up to set email alerts
|

All-Atom Molecular Dynamics Simulations of Uncharged Linear Polymer Bottlebrushes: Effect of the Brush Sizes and the Number of Side-Chain Monomers

Tanmay Sarkar Akash,
Raashiq Ishraaq,
Siddhartha Das

Abstract: Bottlebrush polymers (BBPs), characterized by grafted polymer side chains on linear backbone polymer chain, have emerged as a unique and versatile class of macromolecules with extensive applications in the fields of material science, electronics, battery materials, self-healing technology, etc. In this paper, we employ all-atom molecular dynamics (MD) simulations to present a comprehensive study of poly(methyl methacrylate)-gpoly(2-ethyl-2-oxazoline) (PMMA-g-PEtOx) BBP and its structural and hydration properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…8(a)] for varying side and main chain lengths. 133 Our results revealed that the radius of gyration ( R g ) of the BBPs scale with the length (or the number of monomers) of the side chains ( N SC ) as R g ∼ N α SC for longer side chains (with α = 0.52–0.58 for all values of the size of the backbone or N BB ), whereas R g ∼ N β SC for shorter side chains ( β = 0.36 for smaller N BB and β = 0.0 for larger N BB ) [see Fig. 8(b)].…”
Section: Findings From All-atom MD Simulations Of Uncharged Polymer B...mentioning
confidence: 99%
“…8(a)] for varying side and main chain lengths. 133 Our results revealed that the radius of gyration ( R g ) of the BBPs scale with the length (or the number of monomers) of the side chains ( N SC ) as R g ∼ N α SC for longer side chains (with α = 0.52–0.58 for all values of the size of the backbone or N BB ), whereas R g ∼ N β SC for shorter side chains ( β = 0.36 for smaller N BB and β = 0.0 for larger N BB ) [see Fig. 8(b)].…”
Section: Findings From All-atom MD Simulations Of Uncharged Polymer B...mentioning
confidence: 99%